2018
DOI: 10.1080/02699931.2018.1464434
|View full text |Cite
|
Sign up to set email alerts
|

The impact of contextual priors and anxiety on performance effectiveness and processing efficiency in anticipation

Abstract: It is proposed that experts are able to integrate prior contextual knowledge with emergent visual information to make complex predictive judgments about the world around them, often under heightened levels of uncertainty and extreme time constraints. However, limited knowledge exists about the impact of anxiety on the use of such contextual priors when forming our decisions. We provide a novel insight into the combined impact of contextual priors and anxiety on anticipation in soccer. Altogether, 12 expert soc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
31
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(37 citation statements)
references
References 19 publications
5
31
1
Order By: Relevance
“…In contrast to their predictions, contextual priors pertaining to the cricket bowler's action tendencies, game state, and field setting did not alter the batters' perceived cognitive load. These findings align with those reported in studies by Broadbent et al (2018) and Runswick et al (2017) in which RSME was used to assess the processing demands of using contextual priors during anticipation tasks in soccer and cricket, respectively. Furthermore, Runswick et al (2018a) implemented a backward-counting task in their design, in order to test the impact of contextual priors under conditions of increased task load.…”
Section: Task Loadsupporting
confidence: 88%
See 3 more Smart Citations
“…In contrast to their predictions, contextual priors pertaining to the cricket bowler's action tendencies, game state, and field setting did not alter the batters' perceived cognitive load. These findings align with those reported in studies by Broadbent et al (2018) and Runswick et al (2017) in which RSME was used to assess the processing demands of using contextual priors during anticipation tasks in soccer and cricket, respectively. Furthermore, Runswick et al (2018a) implemented a backward-counting task in their design, in order to test the impact of contextual priors under conditions of increased task load.…”
Section: Task Loadsupporting
confidence: 88%
“…However, the performance improvement on congruent trials was not found when the secondary task was included. In contrast to the studies by Runswick et al (2018a) and Broadbent et al (2018), the increased task load supressed the performance-enhancing effects of contextual priors as participants had to consider dynamic priors in order to use the stable contextual priors effectively. This interplay between different sources of contextual priors, and kinematic information, appears to be a more demanding process and therefore when a cognitively demanding secondary task was introduced participants were less effective in their use of priors.…”
Section: Task Loadmentioning
confidence: 72%
See 2 more Smart Citations
“…Con relación a las variables tácticas, fueron encontrados efectos perjudiciales de la fatiga mental sobre la sincronización entre los jugadores de motivational consequences marked by rewards and losses in high-level of performance. 29 In this sense, research has shown that mental effort prior 30 to or simultaneous 31 to a physical task, as well as stress and anxiety 32 cause changes in soccer performance. Thus, considering cognitive and psychological demands of soccer, it is assumed that the cognitive engagement of players to give practical solutions to the game may cause mental fatigue.…”
Section: Introductionmentioning
confidence: 99%